2018
DOI: 10.14260/jemds/2018/31
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Mean Platelet Volume and Platelet Distribution Width in Risk Categories of Dengue Fever- A Pilot Study

Abstract: BACKGROUNDIncidence of dengue fever is on rise in India. We investigated the characteristics of Mean Platelet Volume (MPV) and platelet distribution width (PDW) in various risk categories of dengue fever. MATERIALS AND METHODSIn this prospective two months pilot study, 100 cases of NS1 antigen and IgM ELISA positive dengue were included. Platelet count for risk categorisation, MPV and PDW values were recorded. Statistical analysis was done using ANOVA (Fisher's test). RESULTSThere were 77%, 18% and 5% cases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…13,15,22 MPV patterns showed a range of 8.7 -13.2 but differed in others. 6,13,15,21,23 The average MPV was in accordance with few studies like Basher et al & Pritam Sewakdar et al 6,10,14 but varied in others like Gogaram et al 19,24,25 MPV patterns were similar to the study by Ishito et al thrombocytopenia patterns were in accordance with the same 3 but varied in others. 2,4 Our study showed a high MPV in increased proportion of thrombocytopenia cases in accordance with few 24,25 but differed in others 21 we had a predominance of high MPV associated with severe thrombocytopenia and high hematocrit as per the WHO criteria for severe dengue.…”
Section: Discussionsupporting
confidence: 86%
“…13,15,22 MPV patterns showed a range of 8.7 -13.2 but differed in others. 6,13,15,21,23 The average MPV was in accordance with few studies like Basher et al & Pritam Sewakdar et al 6,10,14 but varied in others like Gogaram et al 19,24,25 MPV patterns were similar to the study by Ishito et al thrombocytopenia patterns were in accordance with the same 3 but varied in others. 2,4 Our study showed a high MPV in increased proportion of thrombocytopenia cases in accordance with few 24,25 but differed in others 21 we had a predominance of high MPV associated with severe thrombocytopenia and high hematocrit as per the WHO criteria for severe dengue.…”
Section: Discussionsupporting
confidence: 86%
“…Most of the guidelines for treatment of dengue advocated prophylactic platelet transfusion without hemorrhagic manifestations at platelet level 10,000-20,000/cu.mm [6]. Kumar, et al also marked patients with platelet count below 20,000/cu.mm as high risk patients [7].…”
Section: Resultsmentioning
confidence: 99%
“…Mature platelets become greater and more dynamic when platelet production decreases, and MPV levels rise [22]. Expanded MPV related to a consistent platelet count might show heling, however industriously brought MPV up related to proceeded with thrombocytopenia might demonstrate dynamic sickness causing platelet obliteration and the requirement for platelet transfusion [23]. Patients with haemorrhagic propensities have lower MPV levels joined with serious thrombocytopenia (20,000 platelets/Ul) could be an admonition indication of dengue fever and sign the requirement for red cell transfusion [24].…”
Section: Role Of Mean Platelet Volumementioning
confidence: 99%